A systematic review on traditional medicine Toddalia asiatica (L.) Lam.: Chemistry and medicinal potential - Zhi Zeng; Rui Tian; Jia Feng; Nian-an Yang; Lin Yuan (Elsevier, 2021)
Toddalia asiatica (L.) Lam., belonging to Toddalia genus of Rutaceae family, is a folk medicine in China used for hundreds of years. The whole plant can be used as medicine, especially the root that used to be applied in the folk. In recent decades, with the in-depth research from domestic and foreign researchers, it has gradually been discovered that the chemical components in T. asiatica are mainly coumarins and alkaloids. Its pharmacological effects are manifested in anti-inflammatory and analgesic, hemostatic coagulation, anti-tumor, treatment of cardiovascular diseases, etc. It has a wide range of clinical applications and significant effects on rheumatism, pain, wound bleeding, and bruises. Due to its important research value, in this article, the chemical compositions and pharmacological effects of T. asiatica are comprehensively expounded in recent years in order to provide a reference for the related research and application of this medicinal material, which were carried out through a bibliometric search using the Science Citation Index- Expanded (SCIE) database, web of science, Google scholar and Chinese National Knowledge Infrastructure (CNKI) and all that.